Willingness to pay and price elasticity of demand for long-acting injectable cabotegravir among men who have sex with men in Guangxi, China - Chen, Shiwen; Ruan, Yuhua; Liu, Lu; Pei, Hengyan; Jiang, Yu; Huang, Tengda; Wei, Yuxia; Qin, Litai; Dai, Xuebin; Liu, Yu; Liu, Junhui; Xie, Yihong (Frontiers in Pharmacology, 2024)
Objectives: There is still no study focused on willingness to pay for long-acting injectable Cabotegravir (CAB-LA) after it was available on the market in the United States in 2021. Here we explored the willingness to pay for CAB-LA and associated factors, and price elasticity of demand (PED) of CAB-LA among men who have sex with men (MSM) in Guangxi, China.A cross-sectional study was conducted. Univariate and multivariate ordinal logistic regression were performed to explore associated factors of willingness to pay for CAB-LA. PED was used to measure the change in the number of participants willing to pay to a change in price.Results: A total of 1006 MSM were recruited, among which 84.1% was aged between 18-39 years old. The median (interquartile) of the maximum amount of willing to pay for CAB-LA was 200 (100-500) Chinese yuan (CNY) per month. Most (84.2%) were willing to pay less than 600 CNY per month. The number of participants willing to pay for CAB-LA significantly increased as the price decreased. When the price (CNY per month) dropped from 600 to 500, 500